Ibudilast-Induced Decreases in Cytosolic Ca2+ Level and Contraction in Rat Aorta - Takeharu Kaneda; Yasushi Konno; Norimoto Urakawa; Shinjiro Nakajyo; Kazumasa Shimizu (Elsevier, 2007)
The mechanism by which ibudilast induces vasodilation was examined in isolated endothelium-denuded rat aorta. Ibudilast inhibited the contractions induced by phenylephrine (PE) and high K+ with decrease of [Ca2+]i level in a concentration-dependent manner, to the same degree. 3-Isobutyl-1-methylxanthine (IBMX) inhibited PE-induced contraction and [Ca2+]i level in a concentration-dependent manner, but it inhibited high K+-induced contraction without decrease of [Ca2+]i level. In comparison with IBMX, the increases of cAMP and cGMP contents in ibudilast were much smaller than that of muscle tension. Ibudilast did not inhibit 12-deoxyphorbol 13-isobutyrate (DPB)-induced contraction in the presence of verapamil. Treatment with 30 µM ibudilast inhibited the extracellularly added Ca2+-induced muscle tension and increases in [Ca2+]i level during high K+ depolarization. These results suggested that ibudilast inhibited PE- and high K+-induced muscle contractions mainly by the inhibition of [Ca2+]i level in endothelium-denuded rat aorta. Keywords:: ibudilast, smooth muscle, cAMP, cGMP, rat aorta